2018
DOI: 10.1007/s00464-018-6197-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of robotic-assisted laparoscopic versus open lateral lymph node dissection for locally advanced low rectal cancer

Abstract: The short- and long-term outcomes indicated that RALLD may be a useful modality for locally advanced low rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 27 publications
1
45
1
Order By: Relevance
“…Furthermore, we evaluated the parameters for predicting recurrence by DFS, and it showed surgical methods, CRM involvement, and histologic grade were independent factors for recurrence in these patients. Our RS group had significantly lower postoperative local recurrence and better DFS compared with other groups, which was consistent with a previous 54-month follow-up study conducted by Yamaguchi et al [30]. The probable reason for this may be the less CRM involvement in RS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we evaluated the parameters for predicting recurrence by DFS, and it showed surgical methods, CRM involvement, and histologic grade were independent factors for recurrence in these patients. Our RS group had significantly lower postoperative local recurrence and better DFS compared with other groups, which was consistent with a previous 54-month follow-up study conducted by Yamaguchi et al [30]. The probable reason for this may be the less CRM involvement in RS patients.…”
Section: Discussionsupporting
confidence: 91%
“…The postoperative rectal cancer recurrence rate has been significantly reduced, and the postoperative survival rate has been significantly improved since Heald and Ryall presented the concept of a TME [3,13] . In 2009, Hohenberger et al proposed the standardized application of the CME in the radical resection of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yamaguchi et al. showed an excellent 5‐year local relapse‐free survival rate of 98.6% in robotic LLND compared with 90.9% in open LLND ( P = 0.029) …”
Section: Extended Proceduresmentioning
confidence: 99%
“…Only a few studies have reported on long‐term outcomes because of the comparatively short history of RALS for rectal cancer. RALS was compared with CLS in four studies and with OS in two studies . Kim et al.…”
Section: Long‐term Outcomesmentioning
confidence: 99%